Short Communication: IgE production-suppressing effect of asam kandis (dried Garcinia xantochymus) extracts by mouse hybridoma aDNP-Hy Cells - NADYA SUPARDI; ANTON SUMARPO; RICHARD SUTEJO; AGUS BUDIAWAN NARO PUTRA; NAOKI KAGEYAMA; MIHO KAWANO; TAKUYA SUGAHARA (Biodiversitas Journal of Biological Diversity, 2018)
Supardi N, Sumarpo A, Sutejo R, Putra ABN, Kageyama N, Kawano M, Sugahara T. 2018. Short Communication: IgE production-suppressing effect of asam kandis (dried Garcinia xantochymus) extracts by mouse hybridoma aDNP-Hy Cells. Biodiversitas 19: 330-335. Asam kandis (dried Garcinia xanthocymus Hook.f.ex.T.Anderson) is popularly used as a spice in many Indonesian cuisines. Although Garcinia xanthocymus has been reported to possess various pharmacological properties, its immunologic functions have been poorly studied. Therefore, in this study, we aimed to determine immunoglobulin E (IgE) production-suppressing effect of Asam Kandis extract (AKE) using mouse hybridoma aDNP-Hy cells. AKE was prepared through 24 hours maceration in distilled water. IgE production-suppressing activity of AKE by aDNP-Hy cells was examined in time-wise manner. Cell viability and IgE mRNA expression were assessed using trypan blue assay and qRT-PCR, respectively. IgE production-suppressing activity of heat-treated (100°C) AKE was also examined. As a result, AKE significantly reduced IgE production by aDNP-Hy cells in a concentration-dependent manner both in 24 and 36 h incubation periods. Furthermore, AKE exhibited its IgE production-suppressing activity without any cytotoxicity and also significantly decreased IgE mRNA expression. Heat-treated AKE showed no IgE production-suppressing activity, indicating that the bioactive substances are heat labile. More interestingly, heat-treated AKE showed cytotoxic effect by aDNP-Hy cells. We showed that AKE exhibits IgE production-suppressing effect by aDNP-Hy cells. Further studies are necessary to discover underlying bioactive compounds of asam kandis and substance that responsible for the cytotoxic effect of heat-treated AKE.